2015
DOI: 10.1590/1807-3107bor-2015.vol29.0064
|View full text |Cite
|
Sign up to set email alerts
|

Association between temporomandibular disorders and abnormal head postures

Abstract: This study examines the possible correlation between the prevalence of temporomandibular disorders (TMD) and different head postures in the frontal and sagittal planes using photographs of undergraduate students in the School of Dentistry at the Universidade de Brasília -UnB, Brazil. In this nonrandomized, cross-sectional study, the diagnoses of TMD were made with the Research Diagnostic Criteria (RDC)/TMD axis I. The craniovertebral angle was used to evaluate forward head posture in the sagittal plane, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 19 publications
0
10
0
1
Order By: Relevance
“…Some studies [ 13 , 14 ] found correlation between the presence of symptoms of craniocervical dysfunction and temporomandibular disorders. On the contrary, others [ 11 , 15 ] found no relationship between TMD and head-neck posture.…”
Section: Introductionmentioning
confidence: 94%
“…Some studies [ 13 , 14 ] found correlation between the presence of symptoms of craniocervical dysfunction and temporomandibular disorders. On the contrary, others [ 11 , 15 ] found no relationship between TMD and head-neck posture.…”
Section: Introductionmentioning
confidence: 94%
“…Associations between changes in body posture for people with TMD have been discussed in the literature [4][5][6][7][8][9][10], in terms of a relationship between the muscles of the head and the cervical region and the muscles involved in the stomatognathic system [5]. The shortening of a muscle causes a dislocation of the bone structures in which this muscle is inserted, all other muscles that are inserted in these bone structures will also be altered and so on [11].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, 80 students of the dentistry course were evaluated, using profile radiographs with the same tracings used in the present study and it was concluded that there is no relation between cervical posture and TMD in the sagittal plane. The study by Faulin et al (2015) presented the same outcome, despite using photographs as a analyze measurement.…”
Section: Discussionmentioning
confidence: 63%